HUBUNGAN JARAK TANAM TERHADAP KEMAMPUAN PENEDUHAN TANAMAN DI TAMAN PERKOTAAN - Ni Luh Eka Savitri (BUANA SAINS, 2026)
Urban green open spaces (RTH) provide critical shading and cooling services, yet many tropical cities like Palu have suboptimal planting designs. This study evaluated tree species, planting distance, and spatial patterns in Vatulemo Park (20,000 m²) using a survey method. Planting distances (n=34 trees), canopy overlap, and air temperature under shade were measured at 13:00 local time. Pearson correlation analysis was performed. Dominant species were Samanea saman (spacing 25 m) and Terminalia mantaly (spacing 4 m). Canopy overlap occurred only at 4 m spacing. Under-canopy temperatures were 29.3°C (25 m) and 30.4°C (4 m). Correlation was very strong (R = 0.98, p 0.01). Planting pattern followed row arrangement, compliant with Regulation No. 5/PRT/M/2008. However, species richness (26 taxa) is far below the recommended 150. Planting distance significantly affects shading effectiveness. Vatulemo Park requires reduced spacing (4–6 m), canopy overlap, and increased species diversity to optimize thermal comfort.